Experiencias asociativas y autogestionarias en los sectores agrícolas e industrial / Leonel González, Leónidas Pulido, Francisco Guerrero, Marcelino García Q. - González, Leonel Pulido, Leónidas Guerrero, Francisco García Q. Marcelino (1997)
Experiencias asociativas y autogestionarias en los sectores agrícolas e industrial